Analisis Pemasaran Beras di Desa Mangeloreng Kecamatan Bantimurung Kabupaten Maros - Muhmmad Tenri Ajeng; Azisah Azisah; Abd. Asis Pata (Jurnal Agribis, 2025)
The rice marketing system in Mangeloreng village is relatively simple and focuses on local traders. The aim of this research is to determine marketing channels, marketing margins, and the level of marketing efficiency in Mangeloreng Village, Bantimurung District, Maros Regency. This research was carried out in April-July 2024, located in Mangeloreng Village, Bantimurung District, Maros Regency. This type of research is descriptive analysis of the data used in this research is primary and secondary data. Primary data is obtained from data sources that directly provide data to data collectors. In this research, the sampling method used was the snowball sampling method which was carried out by tracing rice marketing channels. The total number of samples was 11 consisting of 1 rice factory, 1 wholesaler, 4 retailers, and 5 final consumers. The results of research on marketing channels, margins, and efficiency levels in Mangeloreng Village, Bantimurung District, Maros Regency are as follows: 1) The marketing channels in this research consist of 3 marketing channels, namely: (a) Rice Producers - Final Consumers (b) Rice Producers - Retailers - Final Consumers (c) Rice Producers - Wholesalers - Retailers - Final Consumers. The highest margin is marketing channel III of IDR 3,000 because it involves wholesalers, retailers, and consumers. The total margin value can be used to determine the efficiency of a marketing pattern. Marketing channel patterns I, II, and III are included in the efficient category, this is because the percentage value of the three channels is in the range of 0 - 33%.